Multimedia Pembelajaran Matematika Interaktif Berbasis Komputer - Kusuma, Rahmat Diyanto Fitri Dwi; Nasution, Sri Purwanti; Anggoro, Bambang Sri (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research has two goals that are to produce a product in the form of interactive computer-based mathematics learning media on linear equations system of two variables and to know the effectiveness of the product that has been developed. This research method is done by using 7 steps as a step to produce the product based on Borg and Gall development model that modified by Sugiyono. Based on the data analysis obtained from material experts and media experts stated that the interactive computer-based mathematics learning media is appropriate to be used based on the validator's validation indicator in which the validator indicator by the material expert is the quality of the content, the accuracy of coverage, language and feasibility of presentation, while the assessment indicator from media experts include visual communications, language, implementation, and software engineering. based on data analysis obtained from learners stated that multimedia learning interactions very good. This means that multimedia interactive computer-based learning that has been developed by researchers can be used as one of the learning resources of students of SMP / MTs class VIII.